Resonance in long-span railway bridges carrying TGV trains. (May 2015) - Gu, Gunmo
Highlights: A railway bridge and the train suspension can be modelled by a virtual structure. The virtual structure includes a set of suspension at every node of the bridge. The virtual structure includes a set of suspension at every node of the bridge. The suspension system fixed to a bridge node is activated or deactivated. Abstract: This research reviews principles behind resonance in long-span railway bridges carrying TGV trains, and introduces a practical method of analysis to determine the degree of resonance and dynamic impact factor under different scenarios. The method is based on a virtual structure consisting of a bridge and a fully articulated train suspension system. The response histories of the train and bridge are computed simultaneously by directly integrating the equation of motion of the entire virtual structure. The method is applied to measure resonance in a realistic model: a 100 m beam-type railway bridge carrying a TGV train, both with appropriate physical characteristics.